Environmentally contingent control of Candida albicans cell wall integrity by transcriptional regulator Cup9. Issue 3 (14th May 2021) - Ichikawa, Yuichi; Bruno, Vincent M; Woolford, Carol A; Kim, Hannah; Do, Eunsoo; Brewer, Grace C; Mitchell, Aaron P
Abstract: The fungal pathogen Candida albicans is surrounded by a cell wall that is the target of caspofungin and other echinocandin antifungals. Candida albicans can grow in several morphological forms, notably budding yeast and hyphae. Yeast and hyphal forms differ in cell wall composition, leading us to hypothesize that there may be distinct genes required for yeast and hyphal responses to caspofungin. Mutants in 27 genes reported previously to be caspofungin hypersensitive under yeast growth conditions were all caspofungin hypersensitive under hyphal growth conditions as well. However, a screen of mutants defective in transcription factor genes revealed that Cup9 is required for normal caspofungin tolerance under hyphal and not yeast growth conditions. In a hyphal-defective efg1 Δ/Δ background, Cup9 is still required for normal caspofungin tolerance. This result argues that Cup9 function is related to growth conditions rather than cell morphology. RNA-seq conducted under hyphal growth conditions indicated that 361 genes were up-regulated and 145 genes were down-regulated in response to caspofungin treatment. Both classes of caspofungin-responsive genes were enriched for cell wall-related proteins, as expected for a response to disruption of cell wall integrity and biosynthesis. The cup9 Δ/Δ mutant, treated with caspofungin, had reduced RNA levels of 40 caspofungin up-regulated genes, and had increased RNA levels of 8 caspofungin down-regulated genes, an indication that Cup9 has a narrow rather than global role in the cell wall integrity response. Five Cup9-activated surface-protein genes have roles in cell wall integrity, based on mutant analysis published previously ( PGA31 and IFF11 ) or shown here (ORF19.3499, ORF19.851, or PGA28 ), and therefore may explain the hypersensitivity of the cup9 Δ/Δmutant to caspofungin. Our findings define Cup9 as a new determinant of caspofungin susceptibility.